Molecular Engineered Hole‐Extraction Materials to Enable Dopant‐Free, Efficient p‐i‐n Perovskite Solar Cells. Issue 18 (12th May 2017) - Chen, Huanle; Fu, Weifei; Huang, Chuyi; Zhang, Zhongqiang; Li, Shuixing; Ding, Feizhi; Shi, Minmin; Li, Chang‐Zhi; Jen, Alex K.‐Y.; Chen, Hongzheng
Abstract : Two hole‐extraction materials (HEMs), TPP‐OMeTAD and TPP‐SMeTAD, have been developed to facilitate the fabrication of efficient p‐i‐n perovskite solar cells (PVSCs). By replacing the oxygen atom on HEM with sulfur (from TPP‐OMeTAD to TPP‐SMeTAD), it effectively lowers the highest occupied molecular orbital of the molecule and provides stronger PbS interaction with perovskites, leading to efficient charge extraction and surface traps passivation. The TPP‐SMeTAD‐based PVSCs exhibit both improved photovoltaic performance and reduced hysteresis in p‐i‐n PVSCs over those based on TPP‐OMeTAD. This work not only provides new insights on creating perovskite‐HEM heterojunction but also helps in designing new HEM to enable efficient organic–inorganic hybrid PVSCs. Abstract : Two hole‐extraction materials (HEMs), TPP‐OMeTAD and TPP‐SMeTAD, are developed for the construction of p‐i‐n perovskite solar cells (PVSCs). Through replacing the oxygen atom with sulfur at the arylamine terminal substituents, TPP‐SMeTAD exhibits superior energetics, charge extraction and trap passivation capabilities to perovskite, over those of TPP‐OMeTAD. It leads to improved photovoltaic performance and reduced hysteresis in TPP‐SMeTAD based p‐i‐n PVSCs.